A NEW SPECIES OF ERIOPHYID MITE FROM BRAZIL (Acari: Trombidiformes) - Mineiro, Jeferson; Flechtmann, Carlos (REVISTA DE AGRICULTURA, 2021)
On a survey of plant mites in the State of SÃ£o Paulo, Brazil, a vagrant eriophyid mite on the leaves of Luffa cylindrica was collected and proved to be new for Science. It is herein described and figured.